MACROECONOMIC FACTORS INFLUENCE THE DISTRIBUTION OF MSME FINANCING IN INDONESIAN ISLAMIC BANKS - Annisa Masruri Zaimsyah; Mariatul Fitri (Airlangga Journal of Innovation Management, 2022)
This study examines macroeconomic factors affecting MSME financing in Indonesian Islamic banks from 2014 to 2021. These factors include inflation, BI rate and exchange rate. The methodology of this study is a quantitative method using the OLS approach. The data used in this study is monthly data from 2014 to 2021. Data was collected from Central Bank and OJK publications. This study found that macroeconomic conditions also affect how MSME financing is channeled in Islamic banks, so inflation and exchange rate partially, but BI Rate does not affect the distribution of MSME financing. This is because Islamic banks do not use an attractive interest rate system but a profit-sharing system. The findings of this study have significant consequences for decision makers, Islamic banks, and market participants. Islamic banks should work more to provide financing for MSMEs. Islamic banks should use innovation and creativity to develop and market new products in MSME financing. Due to its narrow focus on MSME financing in Islamic banks, this research has several limitations including that this research only focuses on macroeconomic factors, many other factors can affect MSME financing such as internal bank factors. Further research can examine the impact of Islamic banking financing on MSME development.